The Patterns of Poisoning Exposure in Different Ages in Duhok Governate: A three Years Study (2016, 2017, 2018) - Noor A. Mohammed (مجلة بغداد للعلوم)
Poisoning with toxic substances accidently or deliberately can be life threatening and especially in some countries that lack the essential tests and facilities to identify the types and causes of these toxic substances. In Iraq, as many other countries, poisoning is one of the chronic public health problems. However, very little literature about the pattern of poisoning cases, types and age is available in Duhok Governorate. Therefore, this study was conducted to determine the most common patterns of poisoning and the related age and gender in Duhok Governorate from 2016-2018, which would possibly contribute to the early diagnosis and treatment of poisoning. The present study was conducted for three years, started from 1st of January 2016 until31st of December 2018. Data were collected from Duhok General Directorate of Health database, based on the data collected from all Duhok Governorate hospitals and health care centers concerning poisoning types, patient’s age and gender. Descriptive statistic was used to analyze the data including (frequency, mean and percentage). A total of 27831 poisoned patients admitted to Duhok city and their districts health centers. Thirteen separated pattern cases of poisoning were recorded. The most common pattern of poisoning cases was food poisoning (61%) in 2016, (75%) in 2017, and dropped to 48% in 2018. In addition to other types of poisoning such as (herbals, sagwa, allergies, metals, organophosphate, rat poising and others) (11.7% in 2016, 4.8% in 2017 and 19.7% in 2018) and scorpion bites (5% in 2016, 5.7% in 2017 and 11.5% in 2018). Poisoning by drugs was the highest in 2018 (667 cases 9.6%) compared to 2017 (574 cases 5.7%) and 2016 (476 cases 4.3%). All other poisoning pattern (insect bite, soaps and other detergents, snake bits, animal’s bits and insecticide) were about or less than 1%. No recorded cases were poisoned by illegal addictive drugs during the period of study. Out of 27831 cases of poisoning, females were much prone to be poisoned than males during the three years 2018, 2017 and 2016. Females were affected by food poisoning (80%) as compared to male (70%). The age between 15-48 years old composed about 43.8% of the total cases, which is the highest % ration among other age groups. In Duhok Governorate, patterns of poisoning in the present study were the first to be documented. The study concludes that the majority of victims were female and food poisons were the most common type. It also seems that less effort is taken from the Committee of Health and Safety Issues. Our study suggests that establishment of specialist poison health centers, and raising awareness among people help effectively to resolve this public problem.